Anthropological explorations in gender : intersecting fields - Dube, Leela (Sage Publications, 2001)
[Anthropological Explorations in Gender] has a clear theoretical thrust and is... perceptive, insightful, analytically sound and well and convincingly expressed... I cannot think of a better synthesis of the complexities of gender in South Asia than is to be found in this book... it would make an excellent classroom text' - The Journal of The Royal Anthropological Institute Leela Dube, a pioneer of feminist anthropology in India, addresses a range of interrelated themes in the study of gender, Kinship and Culture. This book draws upon a variety of distinct and unusual materials to construct ethnographic readings of a feminist imagination. Three substantive themes are addressed in this book. First, the author elaborates issues of growing up female by putting the spotlight on the complex and nuanced processes of the socialization of Hindu girls in patrilineal India. Second, she examines the widely prevalent metaphor of "seed and earth", which represents sexual asymmetry in biological and social reproduction, thereby reinforcing gender inequalities in distinct domains. Third, the author explores the mutual determinations of caste and gender, from the implications of caste for women's lives, to women's roles in maintaining, subverting and changing case.